Molecular characterization and sequence phylogenetic analysis of Babesia bigemina cattle isolate from Mathura based on 18S ribosomal DNA gene - SUDAN, VIKRANT; SHANKAR, DAYA; SHARMA, BARKHA; JAISWAL, AMIT KUMAR; SINGH, AMIT (The Indian Journal of Animal Sciences, 2017)
VSG is considered to be an important molecule for both molecular and serological based detection of surra. Of late, there are reports of variation and/or absence of RoTat 1.2 evansi VSG from a fewer isolates of murine and wild life origin. Hence, in order to use VSG for routine diagnosis of trypanosomiosis, there is need for selection of that portion of gene, which is conserved in all trypanosomes irrespective of species and geographical distribution. Hence, we identified a 205 bp portion of VSG, which is conserved in Trypanosomes.The present communication deals with molecular cloning and characterization of this Trypanozoan specific VSG gene from T. evansi of horse origin from semi arid region of India and checked its uniqueness by comparing it with various other isolates across the world. The selected truncated showed cent percent homology with all other isolates, thereby, justifying its uniqueness.